2021
DOI: 10.14529/jsfi210201
|View full text |Cite
|
Sign up to set email alerts
|

Accelerating Seismic Redatuming Using Tile Low-Rank Approximations on NEC SX-Aurora TSUBASA

Abstract: With the aim of imaging subsurface discontinuities, seismic data recorded at the surface of the Earth must be numerically re-positioned inside the subsurface where reflections have originated, a process referred to as redatuming. The recently developed Marchenko method is able to handle fullwavefield data including multiple arrivals. A downside of this approach is that a multi-dimensional convolution operator must be repeatedly evaluated to solve an expensive inverse problem. As such an operator applies multip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 34 publications
2
13
0
Order By: Relevance
“…Whilst in Hong et al (2021), we focused only on the implementation of the forward batch MVM operation; here, we cover the entire SRI workflow where an iterative solver is used to solve the Marchenko equations. This requires the application of four batch MVM operations as explained in Section 4.…”
Section: Impact On Sri Computational Stagesmentioning
confidence: 99%
“…Whilst in Hong et al (2021), we focused only on the implementation of the forward batch MVM operation; here, we cover the entire SRI workflow where an iterative solver is used to solve the Marchenko equations. This requires the application of four batch MVM operations as explained in Section 4.…”
Section: Impact On Sri Computational Stagesmentioning
confidence: 99%
“…However, whilst this seems to be of vital importance for the former method, the improvement is fairly minor in the latter, making it possible to work with a single or small group of virtual sources at the same time without seriously compromising the quality of the reconstruction. This finding is of great importance for the application of MDD to large-scale, three dimensional datasets where solving for the entire set of virtual sources at the same time may be beyond reach of our current compute capabilities [27], [34]. In order to be able to assess the performance of stochastic MDD against full-gradient MDD, we begin by creating a synthetic, Volve-like dataset.…”
Section: B Synthetic Subsalt Redatumingmentioning
confidence: 99%
“…Once such bases are available, the standard batched MVM step in the MDC operator is replaced by a batched TLR-MVM algorithm (Ltaief et al, 2021;Hong et al, 2021). For each frequency, this is performed in three consecutive phases: (1) the…”
Section: Tile Low-rank Compressionmentioning
confidence: 99%
“…To alleviate the 'curse of dimensionality', these authors showed that by factorizing the kernel matrices of the MDC operator by means of Truncated Singular Value Decomposition (TSVD), they could reduce both the memory footprint and computational cost of applying such an operator in a 2D scenario. Following their claim that similar benefits could be obtained when working with 3D datasets, Hong et al (2021) proposed to apply the so-called Tile Low-Rank (TLR) compression algorithm to the frequency slices of a synthetic 3D dataset.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation